Temporal avoidance as a means of reducing competition between sympatric species - Maziarz, M; Broughton, RK; Beck, KB; Robinson, RA; Sheldon, B (The Royal Society, 2023)
Human activity has modified the availability of natural resources and the abundance of species that rely on them, potentially changing interspecific competition dynamics. Here, we use large-scale automated data collection to quantify spatio-temporal competition among species with contrasting population trends. We focus on the spatial and temporal foraging behaviour of subordinate marsh tits Poecile palustris among groups of socially and numerically dominant blue tits Cyanistes caeruleus and great tits Parus major. The three species exploit similar food resources in mixed groups during autumn–winter. Using 421 077 winter recordings of individually marked birds at 65 automated feeding stations in Wytham Woods (Oxfordshire, UK), we found that marsh tits were less likely to join larger groups of heterospecifics, and they accessed food less frequently in larger groups than in smaller ones. Marsh tit numbers within groups declined throughout the diurnal and winter periods, while the number of blue and great tits increased. However, sites that attracted larger groups of these heterospecifics also attracted more marsh tits. The results suggest that subordinate species exhibit temporal avoidance of socially and numerically dominant heterospecifics, but have limited ability for spatial avoidance, indicating that behavioural plasticity enables only a partial reduction of interspecific competition.